Economic aspects of alcohol consumption in Republic of Ireland - Walsh, BM; Walsh, D (Economic & Social Studies, 1970)
Considerable difficulties beset international comparisons of the incidence and prevalence of 'alcoholism'. This reflects the absence of a universally accepted definition of the illness and of a yardstick by which its occurrence can be objectively established. Some of the various measures that have been proposed or used to compare national rates of alcoholism are obviously of doubtful validity. A brief discussion of these indices is sufficient to establish this point.
Keywords: Health; Alcoholism